The influence of past experience on personality reflected in Emily giffin's where we belong novel (2012) : a psychoanalytic criticism. - Dewi, Septiani Mardiana, Dr. M. Thoyibi, M.S, Mauly Halwat Hikmat, Ph. D (2014)
This study is aimed to show the influence of past experience on personality which is represented by the characters in Where WeBelong novel by Emily Gifiin using psychoanalytic criticism approach. This research is descriptive qualitative research. It is done by veryfying two objectives: the first is analyzing the novel based on its structural elements and the second is analyzing the novel on the psychoanalytic criticism approach. In this method, there are two types of data sources, namely primary data source and secondary data source. The primary data source is Where WeBelong novel (2012) by Emily Gifiin. The secondary data sources are materials other sources such as books, dictionary, internet and journal which is related to the study. The data analysis method is descriptive qualitative analysis based on psychoanalytic criticism. The result of the study are as follows. First, based on the structural analysis of each elements, it shows that the character and characterization, setting, plot, theme, point of view, style are related to each other and establish a unity of pleasant novel. Second, based on psychoanalytic criticism approach, the author reflect the influence of past experience on Marian Caldwell's personality. This novel is an object which explains a secret will be exposed by the truth.